Social and emotional factors as predictors of poor outcomes following cardiac surgery. (4th October 2021) - Cromhout, Pernille Fevejle; Thygesen, Lau Caspar; Moons, Philip; Nashef, Samer; Damgaard, Sune; Berg, Selina Kikkenborg
Abstract: : OBJECTIVES: Existing risk prediction models in cardiac surgery stratify individuals based on their predicted risk, including only medical and physiological factors. However, the complex nature of risk assessment and the lack of parameters representing non-medical aspects of patients' lives point towards the need for a broader paradigm in cardiac surgery. Objectives were to evaluate the predictive value of emotional and social factors on 4 outcomes; death within 90 days, prolonged stay in intensive care (≥72 h), prolonged hospital admission (≥10 days) and readmission within 90 days following cardiac surgery, as a supplement to traditional risk assessment by European System for Cardiac Operative Risk Evaluation (EuroSCORE). METHODS: The study included adults undergoing cardiac surgery in Denmark 2014–2017 including information on register-based socio-economic factors, and, in a nested subsample, self-reported symptoms of anxiety and depression. Logistic regression analyses were conducted, adjusted for EuroSCORE, of variables reflecting social and emotional factors. RESULTS: Amongst 7874 included patients, lower educational level (odds ratio 1.33; 95% confidence interval 1.17–1.51) and living alone (1.25; 1.14–1.38) were associated with prolonged hospital admission after adjustment for EuroSCORE. Lower educational level was also associated with prolonged intensive care unit stay (1.27; 1.00–1.63). Having a high income was associated with decreased odds of prolonged hospital admission (0.78; 0.70–0.87). No associations or predictive value for symptoms of anxiety or depression were found on any outcomes. CONCLUSIONS: Social disparity is predictive of poor outcomes following cardiac surgery. Symptoms of anxiety and depression are frequent especially amongst patients with a high-risk profile according to EuroSCORE. Subj collection: 105, 123 Abstract : Cardiac surgical procedures are being offered to older, more complex and high-risk patients than earlier.